PENGARUH PENGGUNAAN MEDIA APLIKASI KAHOOT! SEBAGAI DIGITAL GAME-BASED LEARNING TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI IPS DI SMA ADABIAH 2 PADANG - Asharnie, Shakira; Wati, Erna (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The research aims to 1). Knowing the learning outcomes of XI social studies class students in the control class at Adabiah 2 Padang High School. 2). To determine the learning outcomes of XI social studies class students in the experimental class at Adabiah 2 Padang High School. 3). To find out the effect of using the Kahoot! application as Digital Game-Based Learning on the learning outcomes of XI social studies class students at Adabiah 2 Padang High School. This type of research is quantitative and based on experimentation. The population in this study were all XI social studies classes at Adabiah 2 Padang High School in the 2023/2024 school year. Withdrawal of samples using purposive sampling, namely taking the entire population with the same characteristics. To produce two sample groups of class XI IPS 2 and class XI IPS 4. Data collection techniques using observation, documentation, and tests, which are in the form of multiple choice totaling 25 items. The research used data analysis techniques of normality test, homogeneity test, t-test, and normalized gain. The results showed that 1). Student learning outcomes in the control class after carrying out the posttest had an average of 74.56. 2). Student learning outcomes in the experimental class after carrying out the posttest had an average of 84. 3). Based on the results of the t-test with a significant level of 5% (0.05) that the tcount ≥ ttable is 2.52 ≥ 2.01, so Ha is accepted and Ho is rejected. Then the N-nomalized gain test gain score of the experimental class is 0.73 while the control class is 0.55. So it can be concluded that the use of Kahoot! application media as digital game-based learning has an effect on student geography learning outcomes.